Synergy of Parents and Christian Early Childhood Teachers: Efforts to Prevent the Negative Influence of Social Media on Early Childhood - Zai, Suardin (Journal of Education and Computer Applications, 2024)
This study discusses the cooperation between parents and Christian PAUD teachers in protecting early childhood from the negative impacts of social media. In this digital era, children are easily exposed to negative content that can affect their development. Synergy between parents and teachers is the key to providing proper education and supervision, so that children can use social media wisely and adhere to Christian values. Therefore, the purpose of writing this article is to provide knowledge discourse to readers, academics, and practitioners to explain the importance of synergy between parents and Christian PAUD teachers in preventing the negative influence of social media on early childhood. The method used in this study is a literature study method with a descriptive qualitative approach through books, journal articles, and websites as references in data collection. The results of this study are parents as the foundation in building children's awareness, while teachers play a complementary role through the transfer of knowledge so that children's innocence can be filled with knowledge and instilling spiritual character for them which can be achieved through synergy between parents and teachers in supporting child development, and especially in preventing the increasingly widespread negative impacts of social media